Synthesis and characterization of zinc-titanium oxide nanoparticles blended methylcellulose derived from Albizia tree as an antibacterial natural polymer composite - Ansam Adnan Hashim; Rashid Jamei (Tikrit Journal of Pure Science)
This paper seeks to synthesize antibacterial green polymeric composites utilizing extracted cellulose, a natural polymer sourced from biomass. The cellulose was obtained from local agricultural waste. Subsequently, the polymeric composites were synthesized, incorporating blends of nano zinc oxide and nano titanium dioxide in varying proportions. All synthesized samples undergo comprehensive characterization and examination through a range of tests encompassing structural and thermal testes. Furthermore, the antibacterial activity of the samples was assessed using the disc diffusion method, enabling the identification of the most effective formulations. The ultimate selection of the optimal composite was based on the collective outcomes of all tests, facilitating its potential utilization across diverse applications. In conclusion, the Albizia tree demonstrates a notable potential for efficient cellulose extraction, making it a viable candidate for such purposes.  The cellulose extracted from Albizia tree holds the capability to yield methylcellulose. The bacterial activity assessment of Nano materials highlighted a distinct efficacy in the case of the 75% Nano TiO2 and 25% Nano ZnO mixture. However, it is worth noting that an excessive increment in Nano ZnO content exhibited adverse effects. Thorough thermal analyses verified the thermal stability of methylcellulose.